Membrane Tethering Complexes in the Endosomal System - Spang, Anne (Frontiers in Cell and Developmental Biology, 2016)
Vesicles that are generated by endocytic events at the plasma membrane are destined to early endosomes. A prerequisite for proper fusion is the tethering of two membrane entities. Tethering of vesicles to early endosomes is mediated by the CORVET complex, while fusion of late endosomes with lysosomes depends on the HOPS complex. Recycling through the TGN and to the plasma membrane is facilitated by the GARP and EARP complexes, respectively. However, there are other tethering functions in the endosomal system as there are multiple pathways through which proteins can be delivered from endosomes to either the TGN or the plasma membrane. Furthermore, complexes that may be part of novel tethering complexes have been recently identified. Thus it is likely that more tethering factors exist. In this review, I will provide an overview of different tethering complexes of the endosomal system and discuss how they may provide specificity in membrane traffic.